Tracing river water versus wastewater sources of trace elements using rare earth elements in the Nakdong River estuarine waters. (November 2020) - Kim, Taejin; Kim, Hayoung; Kim, Guebuem
Abstract: The concentrations of dissolved rare earth elements (REEs) and trace elements (Al, V, Mn, Fe, Co, Ni, Cu, Zn, Mo, Cd, and Pb) were measured along the Nakdong River Estuary. In general, REE concentrations presented negative correlations with salinity, except for the sampling sites close to the wastewater treatment plant (WWTP), where the concentrations were approximately two orders of magnitude higher. In this study, we attempted to utilize REEs as tracers for river versus WWTP sources of trace elements. The main sources of trace elements can be attributed as follows: the seawater for Mo and Cd, the seawater and WWTP for V, the river and WWTP for Ni and Cu, and the WWTP for Al, Mn, Fe, Co, Zn, and Pb. Our results suggest that REEs can serve as powerful tracers for WWTP sources, particularly in coastal waters where various trace element sources are present. Highlights: REEs showed strong inverse correlations with salinity except for WWTP sites. REEs were significantly enriched at WWTP sites compared with the other sites. REEs were utilized as tracers for investigating WWTP sources of trace elements. WWTP could be a significant source of some trace elements.